Lower Intestinal Langerhans Cell Histiocytosis Masquerading as Chronic Malabsorption Syndrome and Failure to Thrive in a Child: A Rare Case Presented with a Succinct Review of Recent Literature - Suryawanshi, Mayur Keshav; Vig, Tanush; Masih, Dipti; Joseph, Reny (Indian Journal of Medical and Paediatric Oncology, 2018)
Langerhans cell histiocytosis (LCH) encompasses a group of disorders characterized by neoplastic proliferation of Langerhans cells causing destruction of tissue, morbidity and mortality. The authors bring forth the case of a 2-year-old child presenting with chronic diarrhea and features of chronic malabsorption that revealed lesions over the ileocolonic mucosa. Histopathological examination with immunohistochemical expression for CD1a confirmed the diagnosis of LCH. Gastrointestinal LCH is quite uncommon, and review of the published English literature revealed about 50 reported cases. The importance of diagnosing this disease is echoed by the grim survival rate of 18 months from the time of diagnosis that is seen in around 60% of cases. Owing to its rarity and unfamiliarity of practicing physicians and pathologists of this disease at this site, the authors wish to discuss the potential pitfalls and differential diagnoses.
Keywords: CD1a; diarrhea; eosinophilic granuloma; malabsorption